Isolation of total RNA of sago pith (top) from peat swamp area - Christina Christy, anak Munan (Universiti Malaysia Sarawak, UNIMAS, 2012)
Metroxylon sagu sp. is mostly found in Sarawak especially in Oya, Mukah, Dalat, Igan, and Balingian districts. It is well established and has become one of the most important industries that contribute to export revenue. In Sarawak, sago palm functions to thrive in the harsh swampy peat environment especially from soil erosion. The extraction of pith from M. sagu is highly associated with hemicelluloses which its major components are xylose and glucose. Thus, this had lead to high content of starch in pith which may enable the study of functional gene expression. Two RNA extraction CTAB methods were used in this studies which are CTAB-LiCl Method I and CTAB-LiCl Method II with some optimization and modification. This is due to the sensitivity of RNA which is very tedious and it degrades easily. The optimization and modification involved including the period of drying process and the frequent of washing step. Total RNA were successfully extracted from both methods. However, CTAB-LiCl Method II was a preferred method due to good and high quality of RNA formed. Clear RNA band was observed when analyzed with 1% agarose gel and viewed under UV light. Hence, the isolation of high yield RNA is important as a first step for the construction of cDNA library in future.